2023
DOI: 10.3390/ijms24055040
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-Associated Muscle Wasting: A Comprehensive Review from Bench to Bedside

Abstract: Sepsis-associated muscle wasting (SAMW) is characterized by decreased muscle mass, reduced muscle fiber size, and decreased muscle strength, resulting in persistent physical disability accompanied by sepsis. Systemic inflammatory cytokines are the main cause of SAMW, which occurs in 40–70% of patients with sepsis. The pathways associated with the ubiquitin–proteasome and autophagy systems are particularly activated in the muscle tissues during sepsis and may lead to muscle wasting. Additionally, expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…[44] For example, systemic inflammation, including sepsis, triggers muscle atrophy via increased proinflammatory cytokines such as TNF-𝛼, IL-6, and IL-1. [45][46][47] Chronic inflammation aggravates muscle weakness and fibrosis in Duchenne muscular dystrophy. [48] Relieving inflammation improves muscle function and reduces muscle fibrosis in mdx mice, a wellknown mouse model of Duchenne muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…[44] For example, systemic inflammation, including sepsis, triggers muscle atrophy via increased proinflammatory cytokines such as TNF-𝛼, IL-6, and IL-1. [45][46][47] Chronic inflammation aggravates muscle weakness and fibrosis in Duchenne muscular dystrophy. [48] Relieving inflammation improves muscle function and reduces muscle fibrosis in mdx mice, a wellknown mouse model of Duchenne muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Critically ill patients, like cystic fibrosis and patients with burns, are highly prone to P. aeruginosa infections, augmenting the adverse effects of these pathologies on skeletal muscle (18)(19)(20). Especially because skeletal muscle constitutes 40% of total body weight and plays numerous vital roles in the human body, including movement, posture maintenance, breathing facilitation, and safeguarding internal organs (21).In previous studies, we have shown that the P. aeruginosa quorum sensing (QS) transcription factor MvfR (Multiple virulence factor Regulator) (22,23), also known as PqsR, is a central QS regulator that controls the expression of multiple virulence genes and the synthesis of many small signalling molecules in this pathogen. MvfR is required for P. aeruginosa full virulence (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Critically ill patients, like cystic fibrosis and patients with burns, are highly prone to Pseudomonas aeruginosa infections, augmenting the adverse effects of these pathologies on skeletal muscle ( 18 20 ). Especially because skeletal muscle constitutes 40% of total body weight and plays numerous vital roles in the human body, including movement, posture maintenance, breathing facilitation, and safeguarding internal organs ( 21 ). In previous studies, we have shown that the P. aeruginosa quorum-sensing (QS) transcription factor MvfR (multiple virulence factor regulator) ( 22 , 23 ), also known as PqsR, is a central QS regulator that controls the expression of multiple virulence genes and the synthesis of many small signaling molecules in this pathogen.…”
Section: Introductionmentioning
confidence: 99%